Design of sweet protein based sweeteners: Hints from structure–function relationships. (15th April 2015) - Rega, Michele Fortunato; Di Monaco, Rossella; Leone, Serena; Donnarumma, Federica; Spadaccini, Roberta; Cavella, Silvana; Picone, Delia
Highlights: The sweet protein MNEI can be used as natural and safe low-calories sweetener. MNEI and its mutants interact with the sweet taste receptor only if properly folded. Structure-guided protein engineering help the design of new low-calories sweeteners. Single chain monellin derivatives Y65R and MNEI are very sweet and thermostable. Y65R exhibits superior sweetness in all experimental conditions tested. Abstract: Sweet proteins represent a class of natural molecules, which are extremely interesting regarding their potential use as safe low-calories sweeteners for individuals who need to control sugar intake, such as obese or diabetic subjects. Punctual mutations of amino acid residues of MNEI, a single chain derivative of the natural sweet protein monellin, allow the modulation of its taste. In this study we present a structural and functional comparison between MNEI and a sweeter mutant Y65R, containing an extra positive charge on the protein surface, in conditions mimicking those of typical beverages. Y65R exhibits superior sweetness in all the experimental conditions tested, has a better solubility at mild acidic pH and preserves a significant thermal stability in a wide range of pH conditions, although slightly lower than MNEI. Our findings confirm the advantages of structure-guided protein engineering to design improved low-calorie sweeteners and excipients for food and pharmaceutical preparations.